Antimicrobial Use Fell Substantially in Japan in 2020—The COVID-19 Pandemic May Have Played a Role. (June 2022) - Ono, Akane; Koizumi, Ryuji; Tsuzuki, Shinya; Asai, Yusuke; Ishikane, Masahiro; Kusama, Yoshiki; Ohmagari, Norio
Highlights: There was a marked reduction in antimicrobial use throughout Japan in 2020. Antimicrobial use was already declining, but this reduction exceeded predictions. Predictions were based on national antimicrobial use trends from 2016–2019. COVID-19 may have contributed to the reduction in antimicrobial use. The possible impact of COVID-19 on appropriate antimicrobial use was explored. Abstract: This study investigated the impact of the COVID-19 pandemic on antimicrobial use (AU) trends in Japan in 2020 and explored its potential effects on appropriate AU. Using nationwide antimicrobial sales data, we examined the annual and monthly trends in AU from 2016–2020 according to the AWaRe classification (Access and Watch categories) and administration route (oral and injectable). To analyze the possible impact of the COVID-19 pandemic on AU, seasonal autoregressive integrated moving average (SARIMA) models were used to predict AU in 2020 (based on the trends from 2016–2019) under the assumption that the pandemic did not occur. We observed a substantial reduction in AU in 2020 compared with preceding years. In addition, the reductions in AU for total antimicrobials and Watch category antimicrobials were greater than predicted regardless of administration route. These results suggest that the COVID-19 pandemic contributed to the observed reductions in AU, but it is also possible that the changes reflect recent efforts to improve AU. Continued AU surveillance and research are needed to optimize prescribing practices through appropriate antimicrobial stewardship.